Emerging Trends in Neuromodulation for Treatment of Drug-Resistant Epilepsy - Abouelleil, Mohamed; Deshpande, Nachiket; Ali, Rushna (Frontiers in Pain Research, 2022)
Epilepsy is a neurological disorder that affects more than 70 million people globally. A considerable proportion of epilepsy is resistant to anti-epileptic drugs (AED). For patients with drug-resistant epilepsy (DRE), who are not eligible for resective or ablative surgery, neuromodulation has been a palliative option. Since the approval of vagus nerve stimulation (VNS) in 1997, expansion to include other modalities, such as deep brain stimulation (DBS) and responsive neurostimulation (RNS), has led to improved seizure control in this population. In this article, we discuss the current updates and emerging trends on neuromodulation for epilepsy.